2022
DOI: 10.1007/s12144-022-03479-z
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of entrepreneurship ecosystem on the entrepreneurial skills of agriculture students: The mediating role of social intelligence and emotional intelligence (The case of University of Zabol, Iran)

Abstract: The present research aimed to analyze the effects of different dimensions of the entrepreneurship ecosystem on the agricultural students' entrepreneurial skills mediated by social and emotional intelligence. The research was conducted among the agricultural students at Zabol University (N = 893) of whom 269 students were sampled by the stratified randomization technique with proportional allocation. The measurement instrument was a questionnaire whose validity was confirmed by a panel of entrepreneurship exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…However, Mortan et al ( 2014) found contradictory results that emotional intelligence does not have an effect on entrepreneurial intention. Karimi and Ataei (2022) confirmed that the success of building entrepreneurship requires people with high emotional intelligence because they can overcome various problems encountered related to the environment and business activities.…”
Section: The Role Of Emotional Spiritual and Social Intelligence On E...mentioning
confidence: 82%
“…However, Mortan et al ( 2014) found contradictory results that emotional intelligence does not have an effect on entrepreneurial intention. Karimi and Ataei (2022) confirmed that the success of building entrepreneurship requires people with high emotional intelligence because they can overcome various problems encountered related to the environment and business activities.…”
Section: The Role Of Emotional Spiritual and Social Intelligence On E...mentioning
confidence: 82%